Нестационарная нагрузка на поверхности упругой полуполосы - Кубенко, В.Д.; Янчевский, И.В. (Прикладная механика, 2015)
Запропонованo методику визначення напружено-деформівного стану пружної півсмуги при дії прикладеного до її межі нестаціонарного навантаження. Сформульовано відповідну граничну задачу з початковими умовами. Застосовано інтегральне перетворення Лапласа і розвинення в ряд Фур’є. Досліджено розвиток напруження і переміщення в часі і за просторовими координатами. A technique is proposed for determination of the stress-strain state of elastic half-strip under action of applied to the boundary non-stationary load. The corresponding boundary problem with initial condition is formulated. The Laplace integral transform is used and further the solution is expanded into Fourier series. A progress of stress and displacement in time and by spatial coordinates is studied.